GUEST INCIVILITY IN SERVICE RECOVERY SITUATIONS: IMPLICATIONS FOR HOTEL ROOM DIVISION EMPLOYEES’ PSYCHOLOGICAL WELL-BEING IN SOUTH SUMATERA - Wisanggeni Agus Priyanto; Luthfia Renalda Tania; Indah Wati; Muhammad Adri Eriyan (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
This study examines the effect of guest incivility during service recovery situations, particularly in complaint handling, on the psychological well-being of room division employees in hotels in South Sumatra. The hospitality industry requires intensive interaction between employees and guests, particularly during complaint handling, which may expose employees to uncivil behavior from guests. Such interactions can create emotional pressure and negatively affect employees’ psychological conditions. This research applied a quantitative approach using structured questionnaires distributed to 100 room division employees working in star hotels across South Sumatra. Data were analyzed using validity and reliability tests, as well as simple linear regression. The findings reveal that guest incivility occurs at a moderate level, with employees frequently experiencing it during service recovery situations, particularly when complaints are delivered impolitely. Psychological well-being indicators also show moderate levels, particularly in emotional exhaustion and psychological distress. The regression analysis shows a correlation coefficient of 0.568 and a coefficient of determination (R²) of 0.323, indicating that guest incivility explains 32.3% of the variance in employees' psychological well-being. These findings highlight that repeated exposure to uncivil guest behavior can significantly influence employees' emotional stability and stress levels. Therefore, hotels should provide organizational support, emotional regulation training, and effective complaint handling systems to protect employees' psychological well-being.